All the PNS is a Stage: Transplanted Bone Marrow Cells Play an Immunomodulatory Role in Peripheral Nerve Regeneration - Piñero, Gonzalo Miguel (2023)
Working on a Wallerian degeneration model in rats, our group has shown the beneficial effects of systemic bone marrow mononuclear cell transplant on morphological and functional parameters, as well as the prevention of neuropathic pain. The current work thus seeks to evaluate the effect of systemic bone marrow cell transplant in a mouse model of sciatic nerve crush and aims to dig deeper into the mechanisms involved in bone marrow cell therapy. Adult C57BL/6J mice were subjected to 8s sciatic nerve crush and intravenously transplanted with bone marrow cells. Cells were tracked using a fluorescent probe, and the evolution of the degeneration–regeneration process was evaluated through axonal and myelin marker immunodetection at different survival times. Gene and protein expression of the main cytokines involved in the inflammatory phase and lesion-associated macrophage phenotypes were also analyzed. Initial findings corroborated the beneficial effect of bone marrow cells on the regenerative process and proved their efficiency in reducing the expression of some proinflammatory cytokines and increasing that of anti-inflammatory interleukin 10 (IL-10). In addition, transplanted animals showed a decrease in inducible nitric oxide synthase (iNOS)+ macrophages, an increment in CD206+ cells, and an anticipated rise in Arg-1+ macrophages. Taken together, our results endorse bone marrow cell therapy as an alternative approach to accelerate nerve recovery and postulate bone marrow cells as potential immunomodulators. Summary Statement: Bone marrow cell transplant has proven to be an effective therapeutic approach to treat peripheral nervous system injuries as it not only promoted regeneration and remyelination of the injured nerve but also had a potent effect on neuropathic pain.